2016
DOI: 10.1177/0894486516682667
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Knowledge Sharing Among Small Family Firm Leaders: A Structural Equation Model

Abstract: Small family firms have many unique relational qualities with implications for how knowledge is passed between individuals. Extant literature posits leadership approach as important in explaining differences in knowledge sharing climate from one firm to another. This study investigates how leadership approaches interact with family influence to inform perceptions of knowledge sharing. We utilise survey data (n = 110) from owner-managers of knowledge-intensive small family firms in Scotland. Our findings presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 137 publications
(192 reference statements)
2
33
0
1
Order By: Relevance
“…Our supporting result, consistent with the stewardship perspective applied to family firms (Corbetta & Salvato, 2004;Davis et al, 1997), underlines the importance of knowledge sharing as a means to translate family members' cognitive and affective attitudes into organizational-level outcomes (e.g., Björnberg & Nicholson, 2012;Chirico & Salvato, 2014;Cunningham, Seaman, & McGuire, 2016;Woodfield & Husted, 2016).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our supporting result, consistent with the stewardship perspective applied to family firms (Corbetta & Salvato, 2004;Davis et al, 1997), underlines the importance of knowledge sharing as a means to translate family members' cognitive and affective attitudes into organizational-level outcomes (e.g., Björnberg & Nicholson, 2012;Chirico & Salvato, 2014;Cunningham, Seaman, & McGuire, 2016;Woodfield & Husted, 2016).…”
Section: Discussionsupporting
confidence: 77%
“…Through this analysis, we extend previous research that has identified heterogeneous family business attributes both as direct predictors of entrepreneurial behavior (Kellermanns & Eddleston, 2006;Kellermanns, Eddleston, Sarathy, & Murphy, 2012) and as factors intervening in knowledge dynamics and knowledge sharing (e.g., Cunningham, Seaman, & McGuire, 2016;Zahra et al, 2007). However, we take one additional step further and suggest that heterogeneity in family business governance should be considered in combination with family members' psychological attitude toward the business to effectively predict outcomes at the organizational level.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…More recent research papers with the application of SEM in these areas are those of Cunningham et al (2017), Putri et al (2017), Khongmalai and Distanont (2017), Smaliukiene et al (2017), and many others. Regardless of the area of the application of SEM, practitioners and theorists agree on five steps involved in testing SEM: model specification, identification, estimation, evaluation and (if needed) modification (Teo et al 2013).…”
Section: Application Of Sem Approach On Firm Performance Research Modelmentioning
confidence: 99%
“…Firstly, further studies could be focused on investigating the transfer of knowledge (Cunningham et al, 2017) in both explicit and tacit (uncodifiable) ways (Hansen, 2002). Additionally, there is room for future research in exploring deeper into the role of macro pressures from outside the firm, which can affect the processes of institutional change.…”
Section: Contributions and Further Developmentsmentioning
confidence: 99%